Iterative, rational design of cyclic and bicyclic peptide inhibitors of matrix metalloproteinases 9 and 2 - Davis, Matthew R. (Tufts Archival Research Center, 2005)
Matrix Metalloproteinases are zinc metalloproteinases involved in cancer progression as well as acute inflammation. Gelatinase A and B, or MMP-2 and MMP-9, are members of this family implicated in extracellular matrix remodeling and angiogenesis. The disulfide-bridged decapeptide CTT is a potent inhibitor of Gelatinases, and has been shown to selectively target tumor cells. This work focused on optimizing a head-to-tail cyclic peptide mimic of CTT, with the aim of improving serum stability as well as affinity to Gelatinases. This was performed via iterative design of a series of peptides testing certain conformational space. In this work, a stabilized cyclic peptide inhibitor of Gelatinases, cWGF9, was found (IC50~49 ï¿½_M). Subsequent series have elucidated its function and specific structural features. In addition, several bicyclic peptide inhibitors based on CTT have been found (IC50~67 ï¿½_M). These peptides have been shown to be more stable in serum and are specific for Gelatinases. Evidence suggests that inhibition of Gelatinases by these compounds may be different than chelation of the active-site zinc.